The Place and Limits of Arbitration in Resolving Employment Disputes in Kenya (Strathmore Law Review, 2025)
Over the last decade, the viability of arbitration in resolving employment disputes has been a controversial issue, attracting mixed views. Proponents argue that Kenyan law neither delimits the scope of arbitrability nor expressly prohibits the use of arbitration in settling employment disputes. They assert that when parties agree to refer their disputes to arbitration, they are bound by the terms of their contracts and the agreement to arbitrate. Opponents, however, contend that employment relationships are inherently unequal. Employers, who often have more bargaining power, impose terms in an employment contract, including arbitration clauses on employees, who are often unduly influenced, to accept such one-sided terms out of necessity to secure jobs. They also argue that arbitration was intended for commercial disputes, not employment disputes. This paper examines the place and limitations of arbitration in resolving employment disputes in Kenya. It critically analyses the legal framework governing employment arbitration to demonstrate that employment disputes can be resolved through arbitration. The paper also identifies the limitations of arbitration in addressing employment disputes and proposes key considerations for courts when deciding whether to refer such disputes to arbitration. Finally, it offers recommendations to enhance the practice of employment arbitration while safeguarding employees’ rights.